Effect Of Social Media Content Quality And Ad Personalization On Student Purchase Intention - Trigina, Lilis; Aqsa, Muhammad; Nadirah, Andi (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to determine and analyze the effect of social media content quality and ad personalization on student purchase intentions. Methodology: This research uses a quantitative approach with a sample of 100 respondents. The data collection technique was carried out using a questionnaire, while data analysis was carried out using statistical methods assisted by SmartPLS software. The tests used include the loading factor test, validity test, reliability test, R-square test, and bootstrapping test. Results: The results indicated that the quality of social media content has a positive but insignificant influence on purchase intention. Ad personalization, on the other hand, has demonstrated a positive and significant impact on student purchase intentions. Findings: Although the influence of social media content quality is individually insignificant, the combination of relevant social media content quality and ad personalization shows a stronger influence on purchase intention. This evidence suggests that both factors play a synergistic role in influencing purchasing decisions. Novelty: This research provides new insights into the synergistic role of social media content quality and ad personalization, both of which can have a greater influence on consumer purchase intentions, especially among university students. Originality: This study introduces an integrated analysis between social media content quality and ad personalization in the context of college students' purchase intention, which has not been widely explored in previous research. Conclusion: The combination of relevant content on social media and personalized ads has the potential to increase consumer purchase intent. Therefore, companies and marketers should consider both simultaneously in order to increase the effectiveness of their marketing campaigns. Type of Paper: Research Paper